Sistem Informasi Perpustakaan Di Smp Negeri 19 Semarang Berbasis Web - Graciano, Joy Arnold; Yusup; Tridian Galih, Sinta (Jurnal Algoritma, 2025)
This study aims to develop a web-based Library Information System at SMP Negeri 19 Semarang. This system is expected to improve efficiency in the process of borrowing, returning, and managing library member data. Currently, these processes are still carried out manually, which causes data inconsistencies and increases the possibility of errors in data collection. The method used is system development using the Waterfall model, with data collection through observation, interviews, and literature study. The developed system is equipped with features such as book borrowing and return records, member data management, and automatic report generation. System testing was conducted using trials to ensure the functionality and ease of use of the system. The results of this study indicate that the developed system can improve library operational efficiency and ease of access for users in accessing books. It is hoped that this system can be implemented to facilitate more efficient and organized library activities in the future.